Maximize your metabolism : lifelong solutions to lose weight, restore energy, and prevent disease - Maclaren, Noel K.; Maclaren, Sunita Singh; Cioffi, Vivian (Grand Central Publishing, 2021)
A pioneering doctor in endocrinology and an expert in diagnostic tools offer a nutrition program based on your body's individual response to insulin paired with exercise and quality sleep, featuring 30 delicious recipes.